THE EFFECT OF BRAND IMAGE AND PRODUCT QUALITY ON MS. GLOW SKINCARE PURCHASE DECISION IN MAKASSAR CITY - Hasdiansa, Ilma Wulansari (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
Service quality plays an important role in a company when competition in the business sector is very tight and continues to change. This study aims to examine the effect of service quality on customer satisfaction, service quality on customer loyalty, customer satisfaction on customer loyalty, and customer satisfaction in mediating the effect of service quality on customer loyalty atIndonesian Sharia Bank. The type of research used is quantitative research and the research design used is causal research design. The subjects in this study were customers atIndonesian Sharia Bankand the objects in this study are service quality, customer satisfaction, and customer loyalty. Data was collected by document recording and questionnaire method, and analyzed byPLS with SmartPLS software. The results showed that service quality has a positive and significant effect on customer satisfaction, service quality has a negative and not significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, and customer satisfaction complete mediation of the influence of service quality on customer loyalty. It is hoped that the results of this research can help future research in paying attention to factors that can influence customer loyalty. It is also hoped that the results of this study will add new knowledge that will enrich marketing management theory and organizational behavior theory, especially those related to customer loyalty.